On Subject Difficulties of Biology Teachers - S. V. Slinkin; E. F. Sadykova; V. V. Klyusova (Научный диалог)
The question of the subject difficulties arising among teachers of biology is considered. Difficulties are revealed as a result of diagnostics of knowledge of students and teachers of KhMAO - Yugra on biology. For this purpose the test tasks formed on the basis of unified state exam and basic state exam (the same for teachers and students) were used. The themes and sections of the school biology course (grades 9 and 11), causing the greatest difficulties for teachers and students, are revealed. A comparison is made between the levels of subject training of teachers and students on the materials of the state final certification of basic general and secondary general education. Special attention is paid to the training of students of pedagogical universities - future teachers of biology. The relevance of the study is determined by the need to effectively organize the training of students of general education institutions to pass the unified state exam and basic state exam on the basis of system-activity approach as a methodological basis of the FSES. The idea is substantiated that during the training of future teachers of biology at the University, during the training of working teachers, special attention should be paid to strengthening the subject and methodological training, as well as strengthening the competence component of the content of biological education, its practical orientation, formation of universal and subject-specific ways of activity.